2020
DOI: 10.18280/ria.340302
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the Art Optimal Multilevel Thresholding Methods for Brain MR Image Analysis

Abstract: The brain MR image analysis is a primary non-invasive component to detect any abnormality in the brain. It is a very important application in the field of medical image processing. For analysing brain MR images, there is a strong need to develop efficient image segmentation methods. Over the years, many image segmentation techniques have been suggested and their real life applications have also been studied. Implementation of these segmentation techniques in biomedical engineering is a major breakthrough. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…What MRI images generate is mainly thermal noise and sometimes physiological noise [21]. Many studies have suggested that it belongs to Rician noise [22], which is strongly correlated with signal [23]. Traditional denoising methods are only suitable for filtering certain types of noise, but not for filtering Rician noise, while wavelet transform has better filtering effect on Rician noise.…”
Section: Image Denoisingmentioning
confidence: 99%
“…What MRI images generate is mainly thermal noise and sometimes physiological noise [21]. Many studies have suggested that it belongs to Rician noise [22], which is strongly correlated with signal [23]. Traditional denoising methods are only suitable for filtering certain types of noise, but not for filtering Rician noise, while wavelet transform has better filtering effect on Rician noise.…”
Section: Image Denoisingmentioning
confidence: 99%
“…These applications underscore the critical role of brain MRI segmentation in advancing medical research and improving patient outcomes. Researchers have proposed various hardware and software methods to address these issues and improve brain MRI segmentation [1]. Generally, softwarebased methods fall into two categories: registration-based and brightness-based.…”
Section: Introductionmentioning
confidence: 99%